Growth Effects of Corn Plants (Zea mays) on Agronomic Aspects of Oil Palm Tree Stands - Ansoruddin, Ansoruddin; Wahyudin Purba, Deddy; Lestari Butar-Butar, Winda; Azhari, M. Nanda; Rafitra, M.Reza; Hidayat Tarigan, Rahmat (Faculty of Agriculture, Universitas Malikussaleh, 2023)
The study aimed to determine the agronomic study of the tolerance of corn plants to conditions shaded by oil palm trees. This research was conducted from July to October 2022. At the Oil Palm Plantation of the Community of Bunut Seberang Village, Asahan Regency, North Sumatra. This study used a factorial randomized block design with two factors and three replications. The first treatment consisted of a shading level (P) with 4 treatment levels namely (P0) without shading, (P1) 35% shading, (P2) 70% shading. The second treatment consisted of a variety of corn (J) with 6 varieties, namely Exsotic Pertiwi (V1), Paragon (V2), Bonanza F1 (V3), Bisi 2 (V4) varieties. The best plant height parameter in the shade level treatment showed 35% shade (P1) resulted in the highest plant height of 113.98 cm, while in the Variety (V4) Bisi-2 variety treatment showed the highest plant, namely 112.83 when compared to other varieties. The effect of various varieties on leaf area showed a significant effect at the age of 6 and 8 WAP. The degree of shade and differences in varieties show the similarity in the quality of the green leaves. The level of shade showed a significant effect on chlorophyll-a and total chlorophyll-a and b where the highest amount of chlorophyll-a was found in the treatment without shade, which was not significantly different from the level of 70% shade, while varieties had a significant effect in producing net photosynthesis formed